Pengembangan Sistem Informasi PPDB Berbasis Web Menggunakan Metode Waterfall Di KB-BA-TPA Restu 2 Malang - Johanes Noel Wijaya; Muhammad Nurwegiono (Universitas Ma Chung, 2025)
KB-BA-TPA Restu 2 Malang previously implemented a conventional new student admission procedure that relied on manual recording and physical file management. This condition resulted in data accumulation and a time-consuming verification process. This study aims to build a web-based registration information system to facilitate school administration and independent registration by parents. The system development was carried out using the Waterfall method, which consists of requirements analysis, system design, coding, and testing stages. System design involved creating flow diagrams and database structures implemented using the PHP programming language and MySQL database. The result of this research is a web application that provides specific interfaces based on user roles, namely administrators, administrative staff, school principals, and parents. The system is equipped with functions for online registration, document and payment validation, interview scheduling, and selection result reporting. The implementation of this system results in the centralization of prospective student data and a structured digital verification mechanism. The conclusion of the study indicates that the developed software is capable of accommodating the school's operational requirements in managing all stages of new student admission, from form filling to graduation announcements.